Snodgrass Tubularized Incised Plate Urethroplasty for Distal and Midpenile Hypospadias - Thapa, B; Pun, M (Journal of Nepal Paediatric Society, 2014)
Introduction: Despite hundreds of repair techniques for hypospadias, the introduction of tubularized incised plate urethroplasty (TIP) by Warren T. Snodgrass has become popular because of good functional and cosmetic outcome. The objective of this study was to share our experience of Snodgrass tubularized incised plate (TIP) urethroplasty for the repair of distal and mid-penile hypospadias. Materials and Methods: This prospective study was carried out for a period of 24 months. It included 46 male patients with the mean age of 4.1 years (18 months to 10 years). Proximal hypospadias and those distal with moderate to severe chordee were excluded. All cases underwent TIP urethroplasty as described by Snodgrass and the neourethra was covered by single or double layer of dorsal prepucial layer. The results were analyzed on the basis of duration of surgery, types of postoperative complications like urethrocutaneous fistula, meatal stenosis and wound dehiscence. Functional results assessed with ease of voiding, force and direction of urinary stream and cosmetic with external look of penis. Results: The overall complication rate requiring surgical intervention was 8 (17.3%). Mean duration of surgery was 66 minutes (60-80 minutes). Urethrocutaneous fistula occurred in 5 (10.8%), meatal stenosis in 1 (2.1%) and wound dehiscence in 2 (4.3%) patient. The cosmetic appearance was excellent in all patients involved in this study except 2 cases of wound dehiscence. All of them had vertically oriented slit like meatus with straight urinary stream. Conclusion: Tubularized incised plate urethroplasty gives good functional and excellent cosmetic results with low rate of complications in distal and mid-penile hypospadias. DOI: http://dx.doi.org/10.3126/jnps.v34i1.8692 J Nepal Paediatr Soc 2014;34(1):29-33